Serosal injury to a distended stomach during open entry for laparoendoscopic single-site surgery - Pei- Chen Chen; Pei- Chen Li; Hsuan Chen; Dah- Ching Ding (Gynecology and Minimally Invasive Therapy, 2022)
Complications related to open entry for laparoscopic procedures are relatively rare, and the incidence of closed entry-related complications is 0.4 per 1000 cases. We report a case of serosal injury to a distended stomach that was caused during open entry. A 37-year-old woman presented with a 1-year history of dysmenorrhea. Transvaginal ultrasonography revealed a uterine myoma and cesarean section (C/S) wound defect. Laparoscopic single-site myomectomy and repair of the C/S wound defect were planned. Open abdominal entry was achieved at the umbilicus, and the patient's stomach was distended and injured by the electric knife (30 watts). After identifying the injury, we inserted a nasogastric tube to deflate the stomach and repaired the gastric serosal injury. The laparoscopic myomectomy and C/S defect repair were subsequently performed without complications. The patient has remained free from complications during the 1-year follow-up. Gastric serosal injury during open entry is a rare complication. Insertion of a nasopharyngeal tube and routine percussion of the abdomen before entering the abdominal cavity are the most important steps to prevent this complication.